HUMANISME DALAM PENDIDIKAN : MEMBANGUN KARAKTER DAN KEMANDIRIAN SISWA SEKOLAH DASAR - Dwi Kartikasari, Febrian (Jurnal Multidisipliner Bharasumba, 2024)
Humanistic education places the human being at the center of the entire learning process, rather than focusing solely on academic achievement or rote memorization. In the context of primary education, this approach becomes an essential foundation for shaping students’ character and independence from an early age. Humanistic education based on Islamic values emphasizes the development of children’s inherent potential (fitrah), noble character, and the habituation of positive behavior through meaningful learning experiences. Children learn not merely to obtain grades, but also to understand themselves, appreciate others, and develop social and spiritual responsibility. This study employs a qualitative approach using a case study at MI Perwanida Blitar. Data collection techniques include classroom observations, interviews with teachers and students, as well as a literature review on humanistic education and Islamic-based character education. Data were analyzed thematically, focusing on how humanistic principles are implemented in teaching practices, classroom management, and character-building activities. The research highlights the role of teachers as facilitators who guide students to think critically, act independently, and develop empathy. The results indicate that the application of humanistic principles in primary education fosters a warm, inclusive learning environment that supports students’ holistic development. Teachers serve as moral exemplars and mentors who provide space for students to express their potential, make autonomous decisions, and learn through practical experiences. Humanistic learning grounded in Islamic values also strengthens students’ spiritual and moral development through activities such as daily prayers, sharing, reflective discussions, and social projects. Students who engage in this approach demonstrate higher levels of independence, critical thinking, and social skills. Thus, Islamic-based humanistic education not only cultivates academically capable students but also develops individuals with strong character, autonomy, and moral and spiritual awareness. The implementation of humanistic principles in primary education is crucial for preparing a generation capable of facing life’s challenges, possessing mature personalities, and contributing positively to society